The effect of sludge age and aerobic sludge mass fraction on low F/M filament bulking in intermittent aeration nitrogen removal systems - Warburton, Charles Arthur (Water Research Group, 2016)
Since 1989 a wide ranging program of research has been under way to identify the factors that effect low F/M filament proliferation. Completed work has established an important factor conducive to low F /M filament proliferation - the presence of anoxic and aerobic zones, or, alternating anoxic-aerobic conditions in a system. It was also established that the presence or absence of readily biodegradable COD (RBCOD) or slowly biodegradable COD (SBCOD) were not deciding factors in their proliferation. The research presented in this thesis focuses on the effects of; • sludge age, • magnitude of the aerobic mass fraction, • magnitude of the nitrate concentration during the anoxic period, on the low F /M filaments. The experimental set-up consisted of two intermittently. aerated anoxic-aerobic (20 minute cycles, peak DO 2 to 2,5 mgO/l), single reactor completely mixed continuously fed systems. The experimental investigation was chronologically divided into 3 phases and examined the effect of the following conditions on the low F/M filaments.